Understanding the Effect of the Third Component PC71BM on Nanoscale Morphology and Photovoltaic Properties of Ternary Organic Solar Cells. Issue 4 (29th January 2020) - Qiu, Beibei; Chen, Shanshan; Sun, Chenkai; Yuan, Jun; Zhang, Xuning; Zhu, Can; Qin, Shucheng; Meng, Lei; Zhang, Yuan; Yang, Changduk; Zou, Yingping; Li, Yongfang
Abstract : Herein, PC71 BM is used as the third component (the second acceptor) to improve the photovoltaic performance of the organic solar cells (OSCs) based on a low‐cost polymer donor PTQ10 and a nonfullerene small‐molecule acceptor Y6. The ternary OSCs based on PTQ10:Y6:PC71 BM reach a higher power conversion efficiency (PCE) of 16.07% with enhanced short‐circuit current density and a better fill factor in comparison with the binary OSCs based on PTQ10:Y6, which is ascribed to the higher electron mobility, better charge extraction, and suppressed charge recombination of the ternary PSCs. The film morphology of the OSCs is studied by grazing‐incidence wide‐angle X‐ray scattering, photo‐induced force microscopy, and transmission electron microscopy, which reveals that with the treatment of additive (0.5% CN) and thermal annealing, the phase separation of Y6 is obviously enhanced, whereas no significant changes occur for that of PTQ10 component. Besides, the addition of PC71 BM slightly lowers the ratio of the face‐on orientation in the blend film and attenuate the aggregation of acceptor Y6. In addition, compared with the binary PTQ10:Y6 OSC, the ternary device based on PTQ10:Y6:PC71 BM shows better device stability, demonstrating a great potential for the practical application of ternary OSCs. Abstract : Ternary organic solar cells (OSCs) based on PTQ10:Y6:PC71 BM demonstrate a higher power conversion efficiency of 16.07% in comparison with the binary OSCs based on PTQ10:Y6. Comprehensive morphology analysis of the blend films is conducted by grazing‐incidence wide‐angle X‐ray scattering, transmission electron microscopy, and photo‐induced force microscopy technologies to understand the morphology evolution during the device optimization.